Tumor renal - Yarisdey Corrales Hernández; Noelia Castro Ladrón de Guevara (Medisur)
<!--[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]--> <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->